PERANAN PEMERINTAH DESA DALAM PEMBANGUNAN PERTANIAN DI DESA KUMPULREJO KECAMATAN KAPAS BOJONEGORO - Witono, Witono; Hidayat, Kliwon; Yuliati, Yayuk (Agros Journal of Agriculture Science, 2024)
This research aims to describe and identify supporting and inhibiting factors in the role of village government and analyze the influence of the role of village government in supporting/inhibiting factors in agricultural development in Kumpulrejo Village, Kapas Bojonegoro District. This type of research includes descriptive qualitative, the presence of the researcher as a research instrument, data mining techniques are carried out using interviews, observations and field notes involving participants as sources of research data. Data analysis techniques are carried out by collecting data, reducing data, presenting data and drawing conclusions. Based on the results of data analysis carried out by the government of Kumpulrejo Village, Kapas Bojonegoro District, it is carrying out its role as Regulator, Dynaminsator, Facilitator and Catalyst in rice development so that rice farming in the village can continue and farmers can more easily obtain agricultural needs. Supporting factors are support from the central government, farmer participation, while the obstacles are limited development funds/budgets and minimal participation in planning.